Bacterial Density, Serotype Distribution and Antibiotic Resistance of Pneumococcal Strains from the Nasopharynx of Peruvian Children Before and After Pneumococcal Conjugate Vaccine 7. Issue 4 (April 2016) - Hanke, Christiane R.; Grijalva, Carlos G.; Chochua, Sopio; Pletz, Mathias W.; Hornberg, Claudia; Edwards, Kathryn M.; Griffin, Marie R.; Verastegui, Hector; Gil, Ana I.; Lanata, Claudio F.; Klugman, Keith P.; Vidal, Jorge E.
Abstract : Background: Pneumococcal conjugate vaccines (PCV) have decreased nasopharyngeal carriage of vaccine types but little data exist from rural areas. We investigated bacterial density, serotype distribution and antibiotic resistance of pneumococcal strains within the nasopharynx of young children in the Peruvian Andes, 2 years after PCV7 was introduced. Methods: Pneumococcal strains were isolated from a subset of 125 children from our Peruvian cohort, who entered the study in 2009 and had pneumococcus detected in the nasopharynx in both 2009 and during follow-up in 2011. Strains were Quellung serotyped and tested for susceptibility to antibiotics. Bacterial density was determined by quantitative polymerase chain reaction. Results: The prevalence of PCV7 strains decreased from 48% in 2009 to 28.8% in 2011, whereas non-PCV7 types increased from 52% to 71.2% ( P = 0.002). There was a 3.5-fold increase in carriage of serotype 6C in 2011 ( P = 0.026). Vaccination with PCV7 did not affect pneumococcal density in children colonized by a PCV7 type but did increase density in those colonized with a non-PCV7 type. Antibiotic resistance did not change after vaccine introduction; strains were nonsusceptible to tetracycline (97.2%), trimethoprim–sulfamethoxazole (56.4%), penicillin (34%), erythromycin (22.4%), chloramphenicol (18.8%) and clindamycin (12.4%). Conclusions: Serotype replacement was observed post-PCV7 vaccination with a concomitant, not previously recognized, increased nasopharyngeal density. Abstract : Supplemental Digital Content is available in the text.